2011
DOI: 10.1073/pnas.1013054108
|View full text |Cite
|
Sign up to set email alerts
|

Receptor activator of NF-κB (RANK) stimulates the proliferation of epithelial cells of the epidermo-pilosebaceous unit

Abstract: Receptor activator of NF-κB (RANK), known for controlling bone mass, has been recognized for its role in epithelial cell activation of the mammary gland. Because bone and the epidermo-pilosebaceous unit of the skin share a lifelong renewal activity where similar molecular players operate, and because mammary glands and hair follicles are both skin appendages, we have addressed the function of RANK in the hair follicle and the epidermis. Here, we show that mice deficient in RANK ligand (RANKL) are unable to ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 55 publications
2
74
0
1
Order By: Relevance
“…Similarly, it has been recently shown that RANK is expressed in several stem cells of the skin, and that RANK signaling activate the hair cycle and epidermal growth (28). The mechanism responsible for this RANK-induced expansion of stem cells remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been recently shown that RANK is expressed in several stem cells of the skin, and that RANK signaling activate the hair cycle and epidermal growth (28). The mechanism responsible for this RANK-induced expansion of stem cells remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…RANKL treatment has been reported to promote proliferation of mammary epithelial cells cultured ex vivo (Kim et al, 2006). Beyond mammary epithelium, recent evidence shows proliferative effects directed by RANKL in other tissues, including the hair follicle pilosebaceous gland (Duheron et al, 2011) and thymus (Lee et al, 2008). Addition of RL stimulated proliferation of NMuMG cells in a dose-dependent manner over 72 hours of culture (Fig.…”
Section: Rank Impacts Anchorage-independent Growth and Survival In Osmentioning
confidence: 95%
“…The fully human monoclonal RANKL-blocking antibody denosumab has been developed and approved for the treatment of osteoporosis and skeletal related events in cancer [10], already benefiting tens of thousands of patients. Besides the crucial function in osteoclastogenesis, RANK and RANKL have been implicated in various other physiological processes including immunotolerance, organogenesis of the immune system [2,3], osteoimmunology [11], hair growth [12] or thermoregulation in the central nervous system [13]. For example, bone loss that frequently occurs under inflammatory conditions such as rheumatoid arthritis can be, in part, explained by RANKL-expressing activated T cells [14].…”
Section: Introductionmentioning
confidence: 99%